2019
DOI: 10.9744/jmk.21.2.95-103
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Total Quality Management on Service Quality, Customer Engagement, and Customer Loyalty in Banking

Abstract: The purpose of the research is to examine the impact of Total Quality Management (TQM)  implementation on  Service Quality, the effect of Service Quality on Customer Engagement and Customer Loyalty in banking industry. The other objective of the research also to examine the effect of Customer Engagement on Customer Loyalty. This research was conducted in East Java Province which involved 209 State Owned Enterprises (SOE) bank customer’s as respondents. All variables are measured by Likert scale from bank custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
4
11
0
1
Order By: Relevance
“…It also shows that empathy is not a major component in increasing CL at Bank Bahteramas in Southeast Sulawesi. This results is supported the research by Junaidi, Rini, and Silalahi (2019); Harimurti and Suryani (2019); who found that empathy has a positive and not significant effect on CL.…”
Section: The Role Of Empathy As Crm Strategy In Increasing CLsupporting
confidence: 89%
“…It also shows that empathy is not a major component in increasing CL at Bank Bahteramas in Southeast Sulawesi. This results is supported the research by Junaidi, Rini, and Silalahi (2019); Harimurti and Suryani (2019); who found that empathy has a positive and not significant effect on CL.…”
Section: The Role Of Empathy As Crm Strategy In Increasing CLsupporting
confidence: 89%
“…It's difficult to differentiate product in banking industry, so service quality become one of the attributes to distinguish bank from another bank. High quality of services enable bank achieving competitive advantage [2] There are many definitions and concept about service quality. Most of previously studies revealed that satisfaction is the result of a process of comparison between customer's expectations and perceptions of performance [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many companies adopt TQM to maintain operational efficiency while securing a competitive advantage (Chang et al, 2010;Simorangkir & Ardiantono, 2022;Zakuan et al, 2008). Its implementation enables the integration of business processes to deliver products or services of the highest quality, thereby meeting and satisfying customer needs and desires, ultimately increasing customer satisfaction (Harimurti & Suryani, 2019;Topalović, 2015;Yu et al, 2020).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Effective implementation of TQM can elevate organizational performance and increase consumer and employee satisfaction (Topalović, 2015). The significance of recognizing quality has expanded the scope of TQM beyond manufacturing and extended its application to the service sector as well (Abdullahi et al, 2020;Harimurti & Suryani, 2019;Ooi et al, 2011;Pattanayak et al, 2017). Nowadays, the TQM system encompasses not only product quality but also extends to encompass the quality of services and the service sector (Abdullahi et al, 2020;Harimurti & Suryani, 2019;Ooi et al, 2011;Pattanayak et al, 2017;Samat et al, 2006).…”
Section: Introduction Backgroundmentioning
confidence: 99%